Policy Implementation of the Karo District Government in Relocation of Communities Affected by the Eruption Gunung Sinabung in Karo Regency, North Sumatra - Mansur Ginting; Asima Yanty Sylvania Siahaan; Hendra Harahap (Budapest International Research and Critics University, 2022)
The purpose of this study was to describe the implementation of the Karo Regency Government's policy in relocating the community as a result of the Gunung Sinabung eruption which was carried out in several stages. The method used in this study is a descriptive type of qualitative method. The technique of determining the informants used purposive sampling technique, as well as data collection by conducting observations and documentation to the relocation location. Based on the research phenomenon related to relocation, described the factors that are considered to influence the implementation of policies according to the theory of George C. Edward III. The results of the study indicate that the implementation of the policies implemented has been going well, although there are still community complaints and problems regarding delays in the construction of residential houses, insufficient availability of farming land, population administration, facilities and infrastructure are not maximized. Supporting factors in the implementation of this policy are standards and targets as well as good relations between organizations and related institutions. Factors that hinder policy implementation are: budget constraints, inadequate relocation land, social conditions and invalid population administration. Recommendations resulting from this research are for the Government to be more active in disseminating policies; propose additional budget to the Central Government, and as soon as possible propose a land use permit for relocation locations to the Central Government